KAJIAN MUTU GIZI BAKSO BERBASIS DAGING SAPI DAN JAMUR MERANG (Volvariella volvaceae) - AGUS PURWANTO PURWANTO '; AKHYAR ALI ALI '; NETTI HERAWATI HERAWATI ' (Jurnal Sagu, 2015)
ABSTRACTThe research aimed to obtain the best treatment and in nutrition, organoleptic test, and methode IndonesianNational Standard (INS). This research used the method Completely Randomized Design (CRD) with fourtreatments and replication. The treatments were D0J0 = 100% beef + 0% Mushroom; D1J1 = 95% + 5%mushroom; D2J2 = 90% + 10% mushroom; D3J3 = 85% + 15% mushroom. Parameters analyzed weremoisture content, ash content, protein content, fiber content and organoleptic values (color, taste, flavor,texture, surface smoothness and overall assessment). The data obtained were analyzed statically usingAnalysis of Variance (Anova) and further tested with Duncan’s New Multiple Range Test (DNMRT) at thelevel of 5%. The treatments gave significant effect on moisture, ash, protein and fiber content as well as onattributes taste and aroma on the hedonic test. The best treatment was D1J1 meatball that have moisture of67%, ash 1,81%, protein 10,13%, and fiber content 0,86% has meet quality standard of meatball SNI 01-3818-1995.Key words: Meatball, beef, mushroom (Volvariella volvaceae)